THE EVOLUTION OF ENGLISH DIALECT IN THE RECENT DIGIAL AGE - Mumek, Geraldy George; Maukar, Merlin M.; Rorimpandey, Rinny S. (Program Studi Pendidikan Bahasa Inggris, 2024)
This research explored the evolution of the English language within the context of the South East Asia Dota II server community players, focusing on the recent digital age. These features of language contributed to the dynamic and evolving nature of English within this digital environment. (1) The study aimed to investigate the influence of social media platforms on vocabulary and lexical choices, as well as the development of new English features within English dialects. (2) Findings revealed that social media platforms significantly impacted vocabulary, introducing internet jargon and abbreviations into regular communication, also Lexical choices were often shaped by the need for brevity and efficiency, leading to the frequent use of acronyms and slang that are influenced by the fluidity of internet. (3) Using a qualitative deeply integrated observation method in Peter Trudgill format, the research examined in-game chat logs, forum discussions, and social media interactions and used a corpus to generalize the research data. (4) from the data that has been gathered from various sources such using corpus, the data analysis reveals that contemporary slang and colloquial terms constitute a significant portion of the corpus, accounting for approximately 6.76% out of the 5759 total words. (5) The research concluded that the digital age, facilitated by social media and online space, played a pivotal role in shaping contemporary English, fostering new linguistic trends and expressions that reflected the global and multicultural interaction among users.